Osteogenic differentiation of adipose-derived canine mesenchymal stem cells seeded in porous calcium-phosphate scaffolds - Herrera, David; Lodoso-Torrecilla, Irene; Ginebra, Maria-Pau; Rappe, Katrin; Franch, Jordi (Frontiers in Veterinary Science, 2023)
Introduction Engineered bone graft substitutes are a promising alternative and supplement to autologous bone grafts as treatments for bone healing impairment. Advances in human medicine extend an invitation to pursue these biomimetic strategies in animal patients, substantiated by the theory that specialized scaffolds, multipotent cells, and biological cues may be combined into a bioactive implant intended for the enhancement of tissue regeneration. Methods This proof-of-concept study was designed to evaluate and validate the feasibility of beta-tricalcium phosphate foam scaffolds seeded with canine mesenchymal stem cells derived from adipose tissue. Cell-inoculated samples and sham controls were cultured statically for 72 hours in complete growth medium to evaluate seeding capacity, while a subset of loaded scaffolds was further induced with osteogenic culture medium for 21 days. Produced implants were characterized and validated with a combination of immunofluorescence and reflection confocal microscopy, scanning electron microscopy, and polymerase chain reaction to confirm osteogenic differentiation in tridimensional-induced samples. Results After 72 hours of culture, all inoculated scaffolds presented widespread yet heterogeneous surface seeding, distinctively congregating stem cells around pore openings. Furthermore, at 21 days of osteogenic culture conditions, robust osteoblastic differentiation of the seeded cells was confirmed by the change of cell morphology and evident deposition of extra-cellular matrix, accompanied by mineralization and scaffold remodeling; furthermore, all induced cell-loaded implants lost specific stemness immunophenotype expression and simultaneously upregulated genomic expression of osteogenic genes Osterix and Ostecalcin. Conclusions β-TCP bio-ceramic foam scaffolds proved to be suitable carriers and hosts of canine adipose-derived MSCs, promoting not only surface attachment and proliferation, but also demonstrating strong in-vitro osteogenic potential. Although this research provides satisfactory in-vitro validation for the conceptualization and feasibility of a canine bio-active bone implant, further testing such as patient safety, large-scale reproducibility, and quality assessment are needed for regulatory compliance in future commercial clinical applications.